Wetland flora of Betkot lake, far western Nepal - Basnet, Ramesh; Luintel, Dolraj; Bhattarai, Krishnaram; Joshi, Mohandev; Sapkota, Kalyan (Journal of Natural History Museum, 2018)
The tropical wetland flora from western Nepal is less explored in comparison to the temperate and alpine region. This study was therefore undertaken to document the vascular plants found on the foot trail of surrounding Betkot Lake, in Chure (Siwalik) hills of Kanchanpur in far western Nepal. The study documented a total of 63 plant species of 40 families belonging to 4 life forms: herbs (31 species), shrubs (14 species), trees (15 species) and climbers (3species). This present study could be a baseline for further research.